Instrumen tes kemampuan representasi matematis materi relasi dan fungsi - Fradinata, Zulkifli; Kartini; Maimunah (Jurnal Pendidik Indonesia, 2025)
Mathematical representation skills are essential for students, as they serve as the foundational ability to develop mathematical thinking and are key to deep conceptual understanding and effective problem solving. However, these skills are often underdeveloped due to the lack of test instruments specifically designed to measure aspects of representation within a particular material context. This study aims to develop test instruments that are valid, reliable, and have appropriate levels of difficulty and discrimination, in order to assess students' mathematical representation skills in relational and functional topics. The research employs a development approach with preliminary and formative evaluation stages adapted from the Tessmer model. The instruments were systematically developed through expert validation, student responses, and field trials involving 31 respondents. The validation process resulted in 14 valid items, with a reliability coefficient of 0.68. The final instrument consists of 3 easy and 11 medium-difficulty questions, with discrimination indices ranging from adequate to very good. These results indicate that the instrument meets the criteria for validity, reliability, appropriate difficulty level, and discrimination power.